Computed tomography-guided biopsy of radiologically unclear lesions in advanced skin cancer: A retrospective analysis of 47 cases. (June 2021) - Franklin, Cindy; Wetter, Axel; Baba, Hideo Andreas; Theysohn, Jens; Haubold, Johannes; Cosgarea, Ioana; Hadaschik, Eva; Livingstone, Elisabeth; Zimmer, Lisa; Stoffels, Ingo; Klode, Joachim; Lodde, Georg; et al.
Abstract: Background: Radiological imaging such as computed tomography (CT) is used frequently for disease staging and therapy monitoring in advanced skin cancer patients. Detected lesions of unclear dignity are a common challenge for treating physicians. The aim of this study was to assess the frequency and outcome of CT-guided biopsy (CTGB) of radiologically unclear, suspicious lesions and to depict its usefulness in different clinical settings. Methods: This retrospective monocentric study included advanced skin cancer patients (melanoma, Merkel cell carcinoma, squamous cell carcinoma, angiosarcoma, cutaneous lymphoma) with radiologically unclear lesions who underwent CTGB between 2010 and 2018. Results: Of 59 skin cancer patients who received CTGB, 47 received CTGB to clarify radiologically suspicious lesions of unclear dignity. 32 patients had no systemic therapy (cohort A), while 15 patients received systemic treatment at CTGB (cohort B). In both cohorts, CTGB revealed skin cancer metastasis in a large proportion of patients (37.5%, 40.0%, respectively), but benign tissue showing inflammation, fibrosis or infection in an equally large percentage (37.5%, 46.7%, respectively). Additionally, a significant number of other cancer entities was found (25.0%, 13.3%, respectively). In patients receiving BRAF/MEK inhibitors, CTGB confirmed suspicious lesions as skin cancer metastasis in 83.3%, leading to treatment change. In immune checkpoint inhibitor-treated patients, skin cancer metastasis was confirmed in 11.1% of patients only, whereas benign tissue changes (inflammation/fibrosis) were found in 77.8%. Conclusions: Our results highlight the relevance of clarifying radiologically unclear lesions by CTGB before start or change of an anti-tumour therapy to exclude benign alterations and secondary malignancies. Highlights: Lesions of unclear dignity are frequent in imaging of skin cancer patients. CT-guided biopsy (CTGB) can be helpful for clarification. Frequency, outcome and clinical impact of CTGB of such lesions were assessed. CTGB revealed >50% unexpected findings (benign findings and secondary carcinomas). CTGB can therefore prevent unnecessary treatment initiation or discontinuation.